A Vindication of the Rights of Woman : With Strictures on Political and Moral Subjects - Wollstonecraft, Mary, 1759-1797 (Salt Lake City, UT : Project Gutenberg, 2002)
"A Vindication of the Rights of Woman" by Mary Wollstonecraft is a feminist essay written in 1792. Wollstonecraft argues that women deserve rational education and fundamental rights equal to men. Responding to eighteenth-century theorists who advocated only domestic education for women, she challenges the view of women as ornaments or property. Instead, she insists women are human beings who should be companions to their husbands and educated contributors to society. This groundbreaking work attacks double standards and launched debates about women's rights that influenced movements for decades to come. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Vindication_of_the_Rights_of_Woman
Release date is 2002-09-01
This etext was produced by Amy E Zelmer, Col Choat, Sue Asscher
Keywords: Feminism; Women's rights -- Great Britain; Women -- Education -- Great Britain; Women -- History -- 19th century